Partial regularity for degenerate variational problems and image restoration models in BV - Schmidt, Thomas (Indiana University Mathematics Journal, 2014)
We establish partial and local C1,α-regularity results for vectorial almost-minimizers of convex variational integrals in BV. In particular, we investigate cases with a degenerate or singular behavior of p-Laplace type, and we cover (local) minimizers of the exemplary integrals ∫ Ω (1 + |∇w|p)1/p dχ with 1 < p < ∞. We also treat some related models with lower-order terms, which are motivated by image restoration. © Indiana University Mathematics Journal.
UnivIS-Import:2015-03-09:Pub.2014.nat.dma.lma2.partia